Pengaruh Emotional Intelligence, Locus of Control, Risk Aversion, dan Financial Literacy Terhadap Risky Investment Intention di Indonesia - Ramadhani, Sekar Savira; Ulpah, Maria; Adawiyah, Wardatul (Jurnal Manajemen dan Usahawan Indonesia, 2025)
This study investigates how individual factors—namely emotional intelligence, external locus of control, risk aversion, and financial literacy—affect the intention to invest in risky financial instruments in Indonesia. The research explores both the direct and indirect effects of these factors on risky investment intentions. Data were collected from 507 respondents through an online questionnaire. The findings indicate that emotional intelligence, external locus of control, and financial literacy positively influence the intention to invest in risky assets, while risk aversion has a negative effect. Additionally, the analysis of indirect effects shows that financial literacy moderates the relationship between emotional intelligence and risk aversion in shaping risky investment intentions. However, financial literacy does not moderate the relationship between external locus of control and risky investment intentions.